Our missing hearts : a novel [compact disc, unabridged] - Ng, Celeste (Reese's book club., 2022)
Twelve-year-old Bird Gardner lives a quiet existence with his loving but broken father, a former linguist who now shelves books in Harvard University's library. Bird knows to not ask too many questions, stand out too much, or stray too far. For a decade, their lives have been governed by laws written to preserve "American culture" in the wake of years of economic instability and violence. To keep the peace and restore prosperity, the authorities are now allowed to relocate children of dissidents, especially those of Asian origin, and libraries have been forced to remove books seen as unpatriotic, including the work of Bird's mother, Margaret, a Chinese American poet who left the family when he was nine years old. Bird has grown up disavowing his mother and her poems; he doesn't know her work or what happened to her, and he knows he shouldn't wonder. But when he receives a mysterious letter containing only a cryptic drawing, he is drawn into a quest to find her. His journey will take him back to the many folktales she poured into his head as a child, through the ranks of an underground network of librarians, into the lives of the children who have been taken, and finally to New York City, where a new act of defiance may be the beginning of much-needed change.